Quality Assessment of YouTube Videos on Complementary and Alternative Medicine (CAM) for Cancer Using a Newly Developed Tool - Sophia Huchel; Alina Grumt; Christian Keinki MD; Judith Buentzel MD; Lukas Käsmann MD; Jutta Huebner MD (Integrative Cancer Therapies)
Background: The global burden of cancer continues to rise and complementary and alternative medicine (CAM) is attracting a lot of interest. However, quality of online information on CAM, particularly on platforms like YouTube, remains questionable. This study aimed to create a comprehensive assessment tool to assess the quality of CAM-related YouTube videos, crucial for informed decision-making in oncology. Methods: The assessment tool was developed by adapting existing criteria for website content analysis to video rating. A YouTube search was conducted using German-language terms related to CAM (“complementary medicine (CM) for cancer” and “alternative medicine (AM) for cancer”). In total 25 videos were assessed based on the defined criteria and assigned to five different types of providers (journalism, healthcare organization, hospital or health insurance, independent person, non-medical organization). Statistical analysis was conducted using IBM SPSS Statistics 27. Results: Interrater reliability analysis showed an Intraclass Correlation Coefficient (ICC) of .91, indicating good to excellent agreement. The average video result was of poor quality, with none of the videos meeting all criteria. The videos achieved a mean rating of 38.2 points (SD: 6.5 points; possible range: 20-60 points). Journalism-based videos showed the most views per days, particularly surpassing those from hospitals or health insurance providers (Kruskal-Wallis-Test: z  = 3.14, P  = .02). However, there was no statistically significant correlation between video quality and the type of provider or interaction indices. Videos retrieved under the search term “CM” generally scored higher in quality than those under “AM” (Mann-Whitney U test: U  = 39.5, P  = .04). Nonetheless, "CM" videos were less frequently viewed (Mann-Whitney U test: U  = 31.0, P  = .01). Conclusion: This study, the first of its kind focusing on CAM in cancer care emphasized the challenges in identifying credible sources on social media platforms such as YouTube. The developed assessment tool offers a more detailed evaluation method for health-related videos but requires further refinement and testing. Collaboration between healthcare and media entities is suggested to improve the dissemination of reliable information on platforms like YouTube.